Clinical manifestations of Johanson-Blizzard syndrome in a patient with nucleotide variants in the UBR1 gene - Jojkić-Pavkov, Danijela; Tošić, Jela; Kavečan, Ivana; Plazačić, Milica (Vojnosanitetski pregled, 2023)
Introduction. Johanson-Blizzard syndrome (JBS) is a very rare genetic disorder caused by a mutation of the ubiquitin protein ligase E3 component N-recognin 1 (UBR1) gene. Clinical diagnosis is based on the pathognomonic combination of congenital exocrine pancreatic insufficiency and characteristic signs of facial dysmorphology (nasal wing hypoplasia/aplasia and oligodontia of permanent teeth). Diagnosis is confirmed by genetic screening of the UBR1 gene. The aim of this case report was to emphasize that nucleotide variants in the UBR1 gene, described as benign or unclassified, should still be considered a genetic cause of the clinical characteristics in patients with JBS. Case report. We present an 8-month-old child, with clinical features of JBS, who was admitted to our hospital due to poor weight gain and loose stools. Upon admission, signs of protein-energy malnutrition, facial dysmorphology, and other anomalies were observed. The child had hypotonia and convergent strabismus. A laboratory examination confirmed exocrine pancreatic insufficiency and hypothyroidism. Genetic testing confirmed two single nucleotide variants in the UBR1 gene – chromosome 15q15.2: NM_174916.3:c.4700+12A>G (intron 42) and NM_174916.3 UBR1:c.862-18C>T (intron 07). A pancreatic enzyme replacement therapy with liposoluble vitamin supplementation and adequate nutrition was conducted. Conclusion. Recognizing the clinical features of JBS and confirming it with genetic analysis is essential, especially in patients with idiopathic pancreatic insufficiency. Even when genetic confirmation is not possible, adequate treatment is necessary for normal growth and development of the child.
Keywords: exocrine pancreatic insufficiency; genes; hypothyroidism; johanson-blizzard syndrome; mutation; ubr1 protein, human